La protection sociale financiarisée selon BlackRock - Camille Noûs (La Nouvelle Revue du Travail)
The present text, written by political economists, criticially assesses a report submitted by BlackRock experts to the French government regarding a potential reorganisation of the country’s pension system. BlackRock is an American multinational specialising in financial asset management. Founded in 1988, it now manages more than $7 billion, a sum 20 times greater than France’s entire state budget and twice as large as the US federal budget. The article looks at the political-economic forces steering, in today’s era of reform, neoliberal governments’ social policy decisions, while deconstructing the political processes that could give birth to systems based on a mandatory capitalisation of pensions. Bearing in mind that present and future retirement incomes have fallen in the UK by anywhere between 20% and 40% since the pension system’s partial capitalisation, the arguments featured in this text have a definite resonance today.